Use of learning theories and visual programming (scratch) in education - Kalogeratos, Gerasimos; Pierrakeas, Christos (Technium Education and Humanities, 2024)
The integration of educational software into education has opened new horizons for learning for both students and teachers. In this particular work we deal with Scratch, which provides students with the opportunity to grasp the concept of interaction between objects while implementing small games. The purpose of the present work was to develop an educational application (Scratch), which can be used as auxiliary material in the elementary school Mathematics lesson, and in particular in mathematics operations related to addition, subtraction and multiplication. Learning Theories related to their integration into educational software are also studied, the main Theories of their use in educational programs are presented and their characteristics are identified.Finally, there are suggestions in this application that use behavioral techniques that are mainly located in the actions of applause or disapproval after each students response.